The Intersection of Max Planck’s Metaphysical Assertion and Christian Theology: A Pragmatic Review of Consciousness and Creation - R. Tjandrawinata, Raymond; B. Atawolo, Andreas (Devotion : Journal of Research and Community Service, 2024)
This systematic review explores the intersection of Max Planck's assertion that "matter is a derivative of consciousness" with key concepts in Christian theology, particularly creation, existence, and the imago Dei. The study aims to investigate how Planck's views align with and enrich theological doctrines, fostering dialogue between science and faith. The objective is to analyze interdisciplinary literature to uncover complementary understandings of the cosmos' origin and nature, drawing from scientific insights and Christian theological frameworks. A qualitative methodology is employed, comprising a systematic analysis of scholarly articles, theological texts, and scientific literature that address consciousness, metaphysics, and divine creation. The findings reveal significant alignment between Planck's concept of consciousness as foundational to matter and Christian beliefs about God’s creative agency and humans as bearers of the imago Dei. This synthesis enhances comprehension of the cosmos as a creation sustained by an underlying consciousness, aligning with the theological principle of divine intentionality. In conclusion, this review highlights the potential for meaningful dialogue between scientific and theological perspectives, offering a unified understanding of existence that bridges the material and metaphysical realms.